Embryonal Carcinoma in Cryptorchid Abdominal Testis of an Infant - Atia Zaka-ur-Rab; Zeeba Zaka-ur-Rab; Kafil Akhtar (Case Reports in Oncological Medicine)
Cryptorchidism is a known predisposing factor for the development of testicular tumors in adults. Age of patient at the time of treatment of undescended testes has some bearing on the risk of neoplasia. Testicular neoplasia at the time of primary surgery for cryptorchidism has been reported rarely in prepubertal period. We report a case where embryonal carcinoma was detected in a cryptorchid testis of an infant.